Threats and Safeguards in the Determination of Auditor Independence - William T. Allen; Arthur Siegel (Washington University Law Quarterly, 2002)
The Article that follows was written before enactment into law of the Sarbanes-Oxley Act. It attempts a brief explication of an existing conceptual framework for determining issues of auditor independence: that of the staff of the Independence Standards Board and suggests that approach is a much sounder way to address remaining issues of auditor independence than the approach reflected in the existing SEC Rule. Because the new Public Company Accounting Oversight Board is charged with addressing issues of auditor independence it will have to try to think conceptually about what we want from a requirement of auditor independence and what we are willing to forego in order to have it. The SEC should encourage it to do so and allow it to replace the political comprise of the existing Rule.
Keywords: Securities fraud; Auditing; Accounting ethics; Auditors; Corporate governance; Securities law